Anisomycin Activates Utrophin Upregulation Through a p38 Signaling Pathway. Issue 5 (7th June 2018) - Hadwen, Jeremiah; Farooq, Faraz; Witherspoon, Luke; Schock, Sarah; Mongeon, Kevin; MacKenzie, Alex
Abstract: Duchenne muscular dystrophy is a recessive X‐linked disease characterized by progressive muscle wasting; cardiac or respiratory failure causes death in most patients by the third decade.  The disease is caused by mutations in the dystrophin gene that lead to a loss of functional dystrophin protein. Although there are currently few treatments for Duchenne muscular dystrophy, previous reports have shown that upregulating the dystrophin paralog utrophin in Duchenne muscular dystrophy mouse models is a promising therapeutic strategy. We conducted in silico mining of the Connectivity Map database for utrophin‐inducing agents, identifying the p38‐activating antibiotic anisomycin. Treatments of C2C12, undifferentiated murine myoblasts, and mdx primary myoblasts with anisomycin conferred increases in utrophin protein levels through p38 pathway activation.  Anisomycin also induced utrophin protein levels in the diaphragm of mdx mice.  Our study shows that repositioning small molecules such as anisomycin may prove to have Duchenne muscular dystrophy clinical utility .